Options for digital twin application in developing country river basin management: a review - Botai, Joel O.; Ghosh, Surajit; Matheswaran, Karthikeyan; Dickens, Chris; Langa, Nkateko; Garcia Andarcia, Mariangel (CGIAR Initiative on Digital Innovation, 2023)
A Digital Twin (DT) is a digital representation of reality. This report explores the implementation of DT in the context of basin scale water management, with a particular focus on developing countries. The review begins with an examination of the background of DT and then delves into successful applications of DT particularly in developing nations. It also explores the potential of integrating Virtual Reality (VR) technologies as a part of DT, emphasizing the importance of stakeholder needs assessment for effective deployment. The review highlights the significance of data infrastructure architecture and data governance in the context of Digital Twins. The review concentrates on the published literature and the application of Digital Twins to river basins, emphasizing their role in decision-making at this level and outlining various use cases for water management. Furthermore, it assesses the expected impact of DT through the lens of the Sustainable Development Goals (SDGs). The review concludes by exploring the integration of Artificial Intelligence (AI) in the context of DT for river basins. Overall, this review summarizes the potential benefits and challenges of implementing DT for water management in developing countries.